ALGORITHM OF INFORMATION PROCESSING IN EVALUATION SYSTEMS TECHNICAL CONDITION OF COMPLEX OBJECTS - Maslovsky , B. G. (Problems of Informatization and Management, 2005)
The paper considers the issues of building a rational and adaptive to the growing volume of current information system for obtaining and processing data on the technical condition of complex systems.